Comparison of Hybrid Rye and Wheat for Grain Yield and Other Agronomic Traits Under Less Favourable Environmental Conditions and Two Input Levels - Thomas Miedaner; Sophie Lauenstein; Bärbel Lieberherr (Agriculture)
Agriculture in the European Union is constantly the subject of public debate, particularly concerning reduced mineral fertilisation and reduced chemical plant protection. Hybrid rye could play a special role in this context, as it usually requires less fertiliser and pesticides than winter wheat and has a high yield potential. In Germany, both crops can be grown on most sites. To test whether hybrid rye is competitive with winter wheat, a trial was conducted with 10 hybrid rye and 20 wheat varieties of all quality levels. The trial was grown for three years (2021, 2022, 2023) on three conventionally managed farms with 40–64 soil points (on a scale of 1–100) in south-west Germany. It was conducted with two input levels: I1, fertilisation (100–120 kg N/ha for hybrid rye; 140–180 kg N/ha for winter wheat), and chemical plant protection including growth regulators; I2, no chemical plant protection, and 20% reduced N fertilisation, one to three harrows. In eight out of nine location × year combinations, hybrid rye was significantly (p < 0.001) superior to winter wheat in terms of grain yield under these conditions. On average, hybrid rye yielded 9.1 and 7.8 t ha−1 for I1 and I2, respectively, compared to 8.0 and 6.8 t ha−1 for wheat, respectively. A close correlation of the cultivar’s grain yield between I1 and I2 for both crops showed a missing cultivar × input level interaction. Under these conditions, hybrid rye produced higher grain yields and better baking quality than wheat in both input regimes, contributing to a more sustainable cropping system.